SELF-DIRECTED LANGUAGE LEARNING USING DUOLINGO - Adwitya Widya Dhari; Syafryadin (PROJECT (Professional Journal of English Education), 2024)
This study explores the effectiveness of Duolingo as a self-directed language learning tool, with a qualitative focus on the experiences of a single participant. Duolingo, offering a wide array of languages and user-friendly features, aligns with Knowles' stages of optimal learning. The participant's motivations, successful learning strategies, challenges, and overall experiences with Duolingo are examined to provide insights into the platform's impact on language acquisition. Motivation is identified as stemming from Duolingo's engaging features and visual simplicity. Learning strategies center around effective time management, with bedtime sessions proving particularly successful. Challenges, such as potential monotony, are addressed through feedback interpretation and practical application with native speakers. The findings resonate with broader research on self-directed language learning, highlighting Duolingo's role in resource management, self-monitoring, and technology dependence. In conclusion, the study underscores Duolingo's efficacy as a self-directed language learning tool, emphasizing its adaptability, engaging features, and capacity to accommodate diverse learning preferences. This research contributes valuable insights to the ongoing discourse on language learning methodologies, offering a nuanced understanding of the dynamic interplay between technology and individual motivation in the evolving landscape of self-directed language learning.